Nutritional Value of Chicken Meat Fed Diet Supplemented with Purslane Rich in Omega-3 Fats. Issue 1 (July 2021) - Kartikasari, L R; Hertanto, B S; Nuhriawangsa, A M P
Abstract: This study aims to examine the effect of dietary supplementation in the form of purslane meal ( Portulaca oleraceae ) as a source of omega-3 fats on the nutritional value of broiler chickens. A total of 180 one-day old unsexed Lohmann broiler chickens was randomly allocated into 30 pens, with each one consisting of 6 chickens. Thereafter the pens were randomly assigned to five experimental diets with 3 replicates (36 birds per treatment). The diets were formulated by adding a basal diet to 0, 1.5, 3.0, 4.5 and 6.0% purslane meal. The water and diets were provided ad libitum throughout the experiment. Furthermore, after 35 days, six chickens per treatment group were slaughtered and processed as carcass. Breast meat were collected for chemical analysis of protein, fat, moisture and collagen using FoodScan Near-Infrared Spectrophotometer, while the data were analysed using ANOVA. Moreover, differences among treatment means were further analysed using Tukey's test. The results showed that diets enriched with omega-3 fats in the form of alpha-linolenic acid had no effect on the collagen content of chicken meat with an average of 1.41%. In addition, the meat protein level which was approximately 22% was the same among dietary treatments. There was also no significant difference in the fat content of meat fed the dietary purslane meal with an average of 2.83%. Based on the results, it was concluded that the nutritional value of broiler chicken meat was not altered by the dietary inclusion level of 6% Portulaca oleracea (purslane) meal as a source of omega-3 fats. Further studies are needed to evaluate whether the supplementation of purslane meal at a higher level is capable of improving the chemical quality of broiler chicken meat.